REVIEW OF GREEN CLOUD-BASED E-LIBRARY SYSTEM DEVELOPMENT FOR REMOTE AREAS IN INDIA (International Journal of Food and Nutritional Sciences, 2022)
This review explores the development of green cloud-based e-library systems tailored for remote areas in India, where access to educational resources remains a significant challenge. As digital technology rapidly advances, creating accessible and environmentally sustainable library systems has become crucial for bridging educational disparities in these underserved regions. The review examines the key requirements for implementing such systems, including the necessary technological infrastructure, internet connectivity, and user accessibility. It also delves into the socio-cultural dynamics that influence the acceptance and effectiveness of these digital libraries, emphasizing the importance of culturally relevant content and community engagement. the review highlights the role of green computing practices in minimizing the environmental impact of digital infrastructure, ensuring that the expansion of educational resources does not come at the cost of increased carbon emissions. By analyzing case studies and existing models, this review identifies best practices and potential challenges in deploying green cloud-based e-library systems. The findings suggest that a well-designed, culturally sensitive, and environmentally sustainable e-library system can significantly enhance educational opportunities, promote socio-economic development, and reduce the digital divide in remote areas of India. This review provides a framework for future efforts to implement similar systems in other underserved regions globally.